2003
DOI: 10.1016/s0006-3495(03)74926-1
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Transition between Single- and Double-Headed Binding of Kinesin as Revealed by Single-Molecule Mechanics

Abstract: Kinesin is a processive motor protein that "walks" on a microtubule toward its plus end. We reported previously that the distribution of unbinding force and elastic modulus for a single kinesin-microtubule complex was either unimodal or bimodal depending on the nucleotide states of the kinesin heads, hence showing that the kinesin may bind the microtubule either with one head or with both heads at once. Here, we found that the shape of the unbinding-force distribution depends both on the loading rate and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
3
44
2
Order By: Relevance
“…We will study the coupling parameter K = κ/2 of the assembly in the following range: We refer to the largest elastic modulus found in [50] for AMP-PNP governed kinesin heads with κ 0.92 pN/nm and therefore limit our calculations to K ≤ 0.5 pN/nm. We choose K ≥ 0.02 pN/nm, since smaller values of K are not convenient: for K < 0.02 pN/nm, the extension of the motor-motor separation L > 160 nm gets large compared to the size of the assembly.…”
Section: Specification Of Parametersmentioning
confidence: 99%
“…We will study the coupling parameter K = κ/2 of the assembly in the following range: We refer to the largest elastic modulus found in [50] for AMP-PNP governed kinesin heads with κ 0.92 pN/nm and therefore limit our calculations to K ≤ 0.5 pN/nm. We choose K ≥ 0.02 pN/nm, since smaller values of K are not convenient: for K < 0.02 pN/nm, the extension of the motor-motor separation L > 160 nm gets large compared to the size of the assembly.…”
Section: Specification Of Parametersmentioning
confidence: 99%
“…Single-molecule detachment experiments confirmed that an ADP-occupied kinesin head binds a microtubule much more weakly than a nucleotide-free or AMPPNP-occupied kinesin head (16)(17)(18). The experimentally determined unbinding force (the force applied to detach kinesin from a microtubule) for the ADP state is Ͻ4 pN (16, 18), whereas the unbinding forces for the empty and AMPPNP states are both Ͼ6 pN (18).…”
mentioning
confidence: 94%
“…P i release occurs at a rate of Ͼ100 s Ϫ1 and is thought not to be rate limiting under any of the conditions mentioned above (4,14). These studies also showed that a kinesin head with an ADP in its nucleotide site binds to the microtubule weakly [K d Ϸ 10-20 M (4)] and that ADP release from the motor head allows it to bind much more strongly to the microtubule (4, 15).Single-molecule detachment experiments confirmed that an ADP-occupied kinesin head binds a microtubule much more weakly than a nucleotide-free or AMPPNP-occupied kinesin head (16)(17)(18). The experimentally determined unbinding force (the force applied to detach kinesin from a microtubule) for the ADP state is Ͻ4 pN (16, 18), whereas the unbinding forces for the empty and AMPPNP states are both Ͼ6 pN (18).…”
mentioning
confidence: 95%
“…A careful investigation of how the binding mode of kinesin depends on the loading rate was performed in the later study (Kawaguchi et al 2003). In this work, the binding in the absence of nucleotides or in the presence of AMP-PNP was tested in a wide range of loading rates (from approx.…”
mentioning
confidence: 99%
“…), that is, slower than the rates of ADP binding and dissociation, as well as the rates of the transition between the singleand the double-headed binding Kawaguchi et al 2003); these conditions ensured that the distributions of the unbinding force exclusively contained the weak, single-headed binding state (ADP-bound) and the strong and also single-headed nucleotide-free binding state. The positions of these two peaks remained constant at all tested ADP concentrations (0, 1, 10, 100 and 1000 mM); however, the relative population of the two states varied with the ADP concentration and, most importantly, depended also on the loading direction, such that the strongbinding peak, corresponding to the unbinding in the nucleotide-free state, appeared at lower ADP concentration under the minus end-directed load.…”
mentioning
confidence: 99%